Interpretation of dichotomous outcomes: sensitivity, specificity, likelihood ratios, and pre-test and post-test probability - Kent, Peter; Hancock, M. (Australian Physiotherapy Association, 2016)
This is the second Research Note in a two-part series on the interpretation of statistical methods used to analyse dichotomous outcomes. The first paper covered risk, odds, risk ratios, odds ratios, and number needed to treat. This paper focuses on sensitivity, specificity, likelihood ratios, and pre-test and post-test probability. These additional measures are calculated from 2 x 2 contingency tables, as were the risk ratios and odds ratios previously covered.